Pengaruh Reputasi Underwriter, Financial Leverage, Profitabilitas dan Ukuran Perusahaan terhadap Underpricing Saham IPO di Bursa Efek Indonesia (BEI) Periode 2022 - Rafieldy, Muhammad; Yusrialis, Yusrialis (MUI Kota Pekanbaru, 2023)
The aim of this research is to determine the influence of underwriter reputation, financial leverage, profitability and company size on the underpricing of IPO shares on the Indonesian Stock Exchange (BEI) for the period 2022. This research is quantitative research that uses secondary data. The population in this study was 59 companies that will IPO in 2022. The total sample was 46 companies using purposive sampling techniques. Data analysis uses time series data regression with the help of SPSS 25. The research results show that the underwriter's reputation influences share underpricing with a significant value of 0.046 < 0.05. Financial leverage influences stock underpricing with a significant value of 0.049 <0.05. Profitability influences stock underpricing with a significant value of 0.003 < 0.05. Company size has no effect on stock underpricing with a significant value of 0.913 > 0.05.